Communicating in Groups: Applications and Skills - Adams Katherine (McGraw -Hill, 2005)
Communicating in Groups offers a concise, step-by-step introduction to the theory and practice of small group communication, and teaches students to develop and apply critical thinking in group problem solving. With the firm belief that group participation can be an uplifting and energizing experience, authors Kathy Adams and Gloria Galanes give students the tools they will need in order to achieve this outcome. Research and theory are presented with a focus on what is important to students--understanding their group experiences and making them effective communicators.